Linguistic Distortion of Hate Speech in the Age of Abundance - Pamungkas, Sri; Muhammadin Al Fath, Ayatollah (Journal of General Education Science, 2023)
The utilization of technology in the era of abundance needs to be balanced with intelligence in managing direction so as not to cause intrigue in society. Cyber ​​crime, including cyber bullying, cannot be separated from the use of language in social media. The language that is used unwisely and even tends to occur linguistic deviations makes the communication building ineffective and even leads to disharmony. This research is important because hate speech, including on social media, has long-term effects that can affect mental, emotional, and physical health. The nature of this research is descriptive by choosing the listening method in providing data. Meanwhile, the data analysis method uses Spradley's ethnographic method, including domain analysis, taxonomy, cultural components and themes.Linguistic deviation in this study is in the form of language forms that are meaningfully and culturally unacceptable. The diction that appears as a form of linguistic deviation refers to insults, slander, divide and conquer, inciting and the like.